2020
DOI: 10.1111/apps.12293
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Intensity, High‐Frequency Intervention to Reduce Procrastination

Abstract: Studies assessing the efficacy of interventions aimed at reducing procrastination have generally lacked robust longitudinal measurement tools. Recent developments in communication technology and applications of the Experience Sampling Method (ESM) have made observations of such dynamic phenomena possible. We leveraged recent advancements in smartphone technology and ESM to measure delay associated with procrastination, while testing a low‐intensity, high‐frequency intervention to reducing that delay. First‐yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition to the practices our workshop participants reported, a sample of which are provided above, material exist in both the scientific literature across various disciplines (e.g., Van Eerde, 2003;Gupta et al, 2012;Andrade, 2013;Manchester and Barbezat, 2013;Prinz et al, 2020;Wessel et al, 2020) and the popular press (e.g., Koch, 1998;Gawande, 2009;McKeown, 2014;Tracy, 2017;Covey, 2020) offering advice on how to have more of your time available to do high-priority tasks and be more productive. Being too busy is so prevalent and worrisome that an industry exists to teach "time management" for individuals, work teams and organizations.…”
Section: Practical Advice Aboundsmentioning
confidence: 99%
“…In addition to the practices our workshop participants reported, a sample of which are provided above, material exist in both the scientific literature across various disciplines (e.g., Van Eerde, 2003;Gupta et al, 2012;Andrade, 2013;Manchester and Barbezat, 2013;Prinz et al, 2020;Wessel et al, 2020) and the popular press (e.g., Koch, 1998;Gawande, 2009;McKeown, 2014;Tracy, 2017;Covey, 2020) offering advice on how to have more of your time available to do high-priority tasks and be more productive. Being too busy is so prevalent and worrisome that an industry exists to teach "time management" for individuals, work teams and organizations.…”
Section: Practical Advice Aboundsmentioning
confidence: 99%
“…Similarly, Troll et al (2020) studied smartphone use as a specific means of procrastination, finding that amount of time spent on the phone was negatively related to grade point average. Wessel et al (2021) showed that the trait of procrastination (akin to action-state dimension of hesitation) was related to academic performance and time spent studying.…”
Section: Introductionmentioning
confidence: 99%